Representasi Komunikasi Persuasif Kepahlawanan Buya Hamka - Muhammad Rizkyka Aghnia Robbani; Askurifai Baksin (UNISBA Press, 2024)
Abstract. Basically humans need communication in dealing with daily life, involving various types of either messages or media. One of the important types of communication in persuasive communication, which has the aim of adjusting individuals they feel and are encouraged to achieve certain goals. Persuasive communication can occur in a variety of contexts, not only during interactions, but also in various circumstances where individuals have certain goals and seek to motivate others to support their achievement. For example, as shown by Buya Hamka in the film “Buya Hamka Vol.I” when he tired to mobilize support for his struggle. This research aims to understand the persuasive communication carried out by Buya Hamka as a hero. This research uses a qualitative method with a Roland Barthes semiotic approach that focuses on the meaning of denotation, connotation, and myth. Abstrak. Pada dasarnya manusia memerlukan komunikasi dalam menghadapi keseharian, melibatkan macam-macam jenis baik itu berupa pesan atau media. Salah satunya jenis komunikasi yang penting adalah komunikasi persuasif, yang memiliki tujuan untuk penyesuaian individu mereka merasa dan didorong unutuk mencapai tujuan tertentu. Komunikasi persuasif bisa terjadi dalam berbagai konteks, tidak hanya saat berinteraksi, tapi juga dalam berbagai keadaan di mana individu memiliki sasaran tertentu serta berupaya memotivasi orang lain untuk mendukung pencapaiannya. Contohnya, seperti yang ditunjukkan oleh Buya Hamka dalam Film